Evaluation of Container Terminal Performance with Capacity Constraint Using System Dynamics - Kurniawan, Fajar; Musa, Siti Nurmaya; Tjolleng, Amir; Ferdian, Rendiyatna (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Container terminal ports are essential in supporting a country's logistics performance. Thus, it is necessary to improve the port's operation to increase its effectiveness. Port operations involve a lot of stakeholders and variables within the system that require all supporting components to be analysed, so a systemic approach is needed. This study investigates an effective decision to improve the performance of container port operations that utilize the system dynamics methodology. Port logistics performance is represented by the leading indicators of port service (service time and stacking yard usage). The results indicate that gate-out rates of container import flow and inaccurate information sharing related to container stacking systems impact port berthing time and yard occupancy ratio.